EFEKTIVITAS PEMANFAATAN KARTU INDONESIA PINTAR DI SMK NEGERI SE-KOTA SURAKARTA - Yosevina Yosevina; Tri Murwaningsih; Patni Ninghardjanti (JIKAP (Jurnal Informasi dan Komunikasi Administrasi Perkantoran), 2022)
This study aims to determine: 1) the effectiveness of the use of the Kartu Indonesia Pintar (KIP) in State Vocational High Schools throughout the city of Surakarta; 2) obstacles that occur in the use of KIP; and 3) solutions given to the problems that occur. This research is a qualitative descriptive research with a case study approach. Sources of research data include informants, documents, and events. The sampling technique was carried out by purposive sampling and snowball sampling. Data was collected by means of interviews, observations, and documents. The validity test technique used is triangulation of techniques and sources. Data analysis techniques with interactive analysis techniques. The results of the study are as follows: The effectiveness of KIP utilization is seen from 1) The accuracy of the target of KIP utilization, in terms of acceptance accuracy is not right because there are still poor KIP holder students who do not get assistance. Meanwhile, in terms of the accuracy of the utilization objectives, it is seen that the funds that have been disbursed by students have been used properly; 2) Socialization of the use of KIP, socialization from the education office is lacking, there is only monitoring once a year. However, socialization to students has been carried out well by the school; and 3) Monitoring of KIP utilization has been carried out by the school through a whatsapp group, from the results of this monitoring the use of KIP in State Vocational Schools throughout the city of Surakarta can be categorized as effective.